Desenvolvimento e aplicação de ferramentas computacionais para análise econômica da produção de óleos essenciais vinculados à extração por arraste a vapor - Silva, João Henrique Santos da (2016)
Brazil has a major plant genetic diversity of the world, consisting of a complex of more than 2 million different species, and therefore a potential for developing country process applied to natural products. The means of production, economic viability and the resources used in the market are gaps to be filled by this sector in order to reach a new level in the international arena. In the organizational context there is great interest in reliable data, as well as concern in generating correct information that also are designed to allow openness to new investment opportunities with relevant important market. It is in this constant process of improving the quality of productivity systems, particularly for the development of new techniques that can be standardized in the search for better results, that mathematical models offer an important advantage, enabling safety aspects in production, exploring the unique features each type of input and making more accurate identification and verification process, with the purpose of result profitability increases and lower costs. Inserted in this scenario, this research seeks to develop a solution in financial and economic model that can add quality and safety in getting better results in extraction processes, by developing a computational tool to estimate cost and price of an essential oil obtained by drag steam. The information generated by the model are intended to verify the performance of three different types of plants: citronella (Cymbopogon winterianus), lemongrass (Cymbopogon citratus) and long pepper (Piper hispidinervum). This software, where the mathematical model was implemented, economic and financial performance of the essential oils extraction process by steam distillation, highlighting what parameters and results are recommended for each plant species evaluated. To achieve the main research objectives were used two combined methodological tools: operational research (adopting the linear programming technique), with a focus on defining a profit maximization objective function and the multi-criteria analysis technique for making investment decisions combining with the methods of Analytic Hierarchy Process (AHP) and Commitment Schedule. The results obtained using the methodology presented maximizing profits for the simulation of long pepper production process (Piper hispidinervum), there was an increase in sales revenue in the order of 2.9% from R$ 226,226.88 to R$ 233,012, 74, with essential oil selling price of long pepper estimated at R $ 214.32 (two hundred and fourteen reais and thirty two cents) and the reference price of 1 liter of hydrolate was R$ 32.13 (20% of the essential oil sales value of long pepper). The decision-making simulations that compared both economic performance, and the production had the kind of citronella as the best economic performance with performance share of 28.50% (0.2850), with the long pepper species 31 12% (0.3112) and capim lemon 40.37% (0.4037) in second and third respectively as the logic of this model. In the production process of the kind of approach Lemongrass obtained the best position with 32.59% performance dimension (0.3259), followed by long pepper 33.50% (0.3349) and Citronella 33.91 % (0.3391) in the last position. The two simulations showed interesting results, under the economic approach species long and Lemongrass pepper need to improve their indicative in relation to the kind of Citronella, since the simulation of production processes all species have very similar results, and thus can be interpreted as a possible technical tie.